TINJAUAN YURIDIS HOLDINGISASI BUMN DALAM RANGKA PENINGKATAN KINERJA MENURUT PERSPEKTIF HUKUM PERUSAHAAN - JOHN SIPAYUNG; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
The government will implement holding process in plantation sector in this year. However, the hindrance found in this holding process is the unavailability of specific regulation governing the forming of holding in company. Having this holding, it will improve the performance of the company and add the profit from new company with the holding. The objective of this research is to know the role of the government in implementing the forming of holding company. The method of research was analysis descriptive research method, that was a research describing a situation or event to search, and then to analyze the event based on the facts from the secondary data obtained from primary law material, secondary law material and tertiary law material. The used research method was yuridical normative analysis, that was by describing and testifying the data related to the problem in company holding. Data collection technique for this research was carried out with library research, literature or documents to get the secondary data. The existence of state-owned corporations is one of real forms in Constitution 1945 especially article 33 with strategic position to increase the prosperity of the people. In the case of holding company that the responsibility of main company to branch company is only limited to the authority given to main company. The responsibility is only on management and policies related to the branch companies. Hence, it is necessary to have one rule governing the holding in specific and the government may understand and know the real process of the holding in state owned corporations. It is intended to improve the performance of state owned corporations related to the income and expenditure of state. Kata Kunci : BUMN, Holding, dan Hukum Perusahaan.